Investigating the Ca2+-dependent and Ca2+-independent mechanisms for mammalian cone light adaptation. Issue 1 (December 2018) - Vinberg, Frans; Kefalov, Vladimir
Abstract Vision is mediated by two types of photoreceptors: rods, enabling vision in dim light; and cones, which function in bright light. Despite many similarities in the components of their respective phototransduction cascades, rods and cones have distinct sensitivity, response kinetics, and adaptation capacity. Cones are less sensitive and have faster responses than rods. In addition, cones can function over a wide range of light conditions whereas rods saturate in moderately bright light. Calcium plays an important role in regulating phototransduction and light adaptation of rods and cones. Notably, the two dominant Ca2+ -feedbacks in rods and cones are driven by the identical calcium-binding proteins: guanylyl cyclase activating proteins 1 and 2 (GCAPs), which upregulate the production of cGMP; and recoverin, which regulates the inactivation of visual pigment. Thus, the mechanisms producing the difference in adaptation capacity between rods and cones have remained poorly understood. Using GCAPs/recoverin-deficient mice, we show that mammalian cones possess another Ca2+ -dependent mechanism promoting light adaptation. Surprisingly, we also find that, unlike in mouse rods, a unique Ca2+ -independent mechanism contributes to cone light adaptation. Our findings point to two novel adaptation mechanisms in mouse cones that likely contribute to the great adaptation capacity of cones over rods.